ERRα fosters running endurance by driving myofiber aerobic transformation and fuel efficiency - Hui Xia; Charlotte Scholtes; Catherine R. Dufour; Christina Guluzian; Vincent Giguère (Elsevier, 2023)
Objective: Estrogen related receptor α (ERRα) occupies a central node in the transcriptional control of energy metabolism, including in skeletal muscle, but whether modulation of its activity can directly contribute to extend endurance to exercise remains to be investigated. The goal of this study was to characterize the benefit of mice engineered to express a physiologically relevant activated form of ERRα on skeletal muscle exercise metabolism and performance. Methods: We recently shown that mutational inactivation of three regulated phosphosites in the amino terminal domain of the nuclear receptor ERRα impedes its degradation, leading to an accumulation of ERRα proteins and perturbation of metabolic homeostasis in ERRα3SA mutant mice. Herein, we used a multi-omics approach in combination with physical endurance tests to ascertain the consequences of expressing the constitutively active phospho-deficient ERRα3SA form on muscle exercise performance and energy metabolism. Results: Genetic heightening of ERRα activity enhanced exercise capacity, fatigue-resistance, and endurance. This phenotype resulted from extensive reprogramming of ERRα global DNA occupancy and transcriptome in muscle leading to an increase in oxidative fibers, mitochondrial biogenesis, fatty acid oxidation, and lactate homeostasis. Conclusion: Our findings support the potential to enhance physical performance and exercise-induced health benefits by targeting molecular pathways regulating ERRα transcriptional activity.